Ciclos económicos y retórica administrativa. Dualidad ideológica en Colombia (2019)
Professors Stephen R. Barley and Gideon Kunda (1992) conducted a study titled: “Design and Devotion: Surges of Rational and Normative Ideologies of Control in Managerial Discourse” in which they found that in the United States management theories are presented in waves of rhetoric which corresponded directly with economic cycles. In this way, theories with rational content (those directed at controlling work) stand out in periods of growth, while those with normative content (those directed at controlling the worker) prevail in times of economic shrinking. Based on these results, and returning to the historical scheme of the appearance of waves of management ideology in Colombia proposed by professor Francisco López G. (1998), a similar study was conducted in which the development of management thinking in Colombia was found to also have a relation to the economic cycle, to emerge in waves, and to have particular characteristics.